Adaptive object placement for augmented reality use in driver assistance systems - Bordes, Lucie; Breckon, Toby P.; Katramados, Ioannis; Kheyrollahi, Alireza (Cranfield University, 2011)
We present an approach for adaptive object placement for Augmented Reality (AR) use in driver assistance systems. Combined vanishing point and road surface detection enable the real-time adaptive emplacement of AR objects within a drivers' natural field of view for on-road information display. This work combines both automotive vision and multimedia production aspects of real-time visual engineering.